Soil Compaction Methods Development - Lvovska, Tetyana; Lytvynenko, Tetyana; Kariuk, Alla (International Journal of Engineering and Technology, 2018)
A process of soil compaction methods development including new authors’ methodology is described. The importance of soil compaction for engineering purposes is substantiated. Preconditions for Proctor compaction test appearance are highlighted. Proctor’s approach and suggestions for the degree of soil compaction assessing are analyzed. Soviet version of Proctor’s equipment and Modified Proctor compaction test are given. Principal differences between Proctor test, Standard compaction test and Modified Proctor test are presented. The problems and disadvantages of existent soil compaction tests are revealed. New authors’ physical experiment methodology for patterns establishment of water migration in subgrade embankment depth, in the capacity factors of what it is accepted: clay soil type (its number plasticity); moisture, at what the soil was compacted; soil skeleton density; embankment height; «rest» time after subgrade erection and before it’s operation is developed and realized. By laboratory and field tests water migration patterns in compacted subgrade soils depth are established. As a result of statistical processing of research results, the empirical dependence of compacted clay soil stabilized moisture is obtained. Empirical dependence parameter corresponds to maximum molecular moisture capacity at what it is advisable to do the subgrade clay soils multilayer consolidation for their long-term strength ensuring.